Continuing professional development : a guide for information professionals - Brine, Alan.; ScienceDirect eBooks (Oxford [England] : Chandos Publishing, 2005)
This book helps information professionals in their continuing professional development (CPD). The book shows them how to examine their own skills and plan their development over a period of time. It also helps them to focus on their career path and begin the acquisition of skills necessary for the route they wish to follow in information work. The book is set against the background of CPD being an essential part of the modern information professional's career planning. Employers are certain to be able to choose between a number of qualified personnel for every available post. Those individuals that have a proven track record of skills development in both their personal and professional skills are more employable.
Introduction -- Skills, strengths and weaknesses -- Using portfolios to record professional development -- Programmes for development -- Support for the developing information professional -- Continuing career development -- Summary.
Includes bibliographical references and index.
Elsevier
Keywords: Library education; Information science -- Study and teaching; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Information science -- Study and teaching; Library education; Electronic books